2022
DOI: 10.12703/r/11-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of epidemic diseases: zoonoses and other origins

Abstract: Infectious diseases emerge via many routes and may need to overcome stepwise bottlenecks to burgeon into epidemics and pandemics. About 60% of human infections have animal origins, whereas 40% either co-evolved with humans or emerged from non-zoonotic environmental sources. Although the dynamic interaction between wildlife, domestic animals, and humans is important for the surveillance of zoonotic potential, exotic origins tend to be overemphasized since many zoonoses come from anthropophilic wild species (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 128 publications
(153 reference statements)
0
11
0
Order By: Relevance
“…More than 60% of human infectious diseases have a zoonotic origin, which underscores the urgent need to promote animal and human diagnostic collaboration under the One Health umbrella in preparation for future pandemics. [23] Colleges and the National Animal Health Laboratory Network member laboratories in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…More than 60% of human infectious diseases have a zoonotic origin, which underscores the urgent need to promote animal and human diagnostic collaboration under the One Health umbrella in preparation for future pandemics. [23] Colleges and the National Animal Health Laboratory Network member laboratories in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic continues to be a major threat to public health security, so do other respiratory infections, such as TB, influenza, fungal and AMR. Whilst COVID-19 still dominates the global public health agenda, the world needs to refocus attention on all respiratory tract infections which have been neglected ever since the emergence of COVID-19 pandemic [11][12][13][14]. New ways of working through alignment of health services and utilizing the latest in diagnostics screening simultaneously for COVID-19, tuberculosis, and other bacterial and viral causes of respiratory tract Infections to screen, confirm, and initiate patients on specific treatment is required.…”
Section: Discussionmentioning
confidence: 99%
“…intra-host pathogen changes) may be impossible to predict and there is little that can be done beyond general prevention strategies. Weiss et al (2022) showed high impact human infections in 2020 including; zoonotic origin, zoonosis or non-zoonosis infections causing mortality. These include important endemic infectious diseases of humans like tuberculosis, contemporary emergent infections (HIV/AIDs) and recent pandemics (COVID-19 and Candida auris) which have caused millions and hundreds of thousands of deaths.…”
Section: Novel Zoonotically Acquired Human Infectionsmentioning
confidence: 99%